SUMMARY REPORT OF NASDA'S EARTHQUAKE REMOTE SENSING FRONTIER PROJECT - Hayakawa M.; Molchanov O.A. (My University, 2004)
After the disastrous Kobe earthquake, the former Science and Technology Agency (STA) of Japanese Government proposed the Integrated Earthquake Frontier Project. Within the framework of this project, two institutions (RIKEN and NASDA (National Space Development Agency of Japan)) were asked to carry out over five years a feasibility study of the use of electromagnetic phenomena in short-term earthquake prediction. Since 1996 the RIKEN group has been engaged in the study of earth current and related phenomena. Meanwhile, under the NASDA project named “Earthquake Remote Sensing Frontier Project”, we performed an overall study of seismo-electromagnetic phenomena occurring not only in the lithosphere, but also in the atmosphere and ionosphere. Our five-year study has yielded that the seismic effect expresses itself not only in the lithosphere (such as by ULF electromagnetic emissions, acoustic emissions etc.), but also in the atmosphere and ionosphere (by means of pre-existing transmitter signals). Most importantly, we find convincing evidence for seismo-ionospheric perturbations on the basis of subionospheric VLF/LF signals. We have established a new challenging science field, “Lithosphere–atmosphere–ionosphere coupling” or “Electromagnetics in the coupled lithosphere–atmosphere–ionosphere system”. The study of this coupling would contribute to the scientific short-term earthquake prediction.